2011
DOI: 10.1177/1420326x11419345
|View full text |Cite
|
Sign up to set email alerts
|

Energy Benefit of the Underfloor Air Distribution System for Reducing Air-Conditioning and Heating Loads in Buildings

Abstract: Although there have been continuing efforts recently for low-energy buildings as parts of the low-carbon green growth movement, particular attention has been paid to architectural design, the elective control of façades, and the efficiency of Heating, Ventilation, and Air Conditioning (HVAC) mechanical systems. To maximize the gains from these efforts, it is essential to consider the energy distribution approach and its layout during the design stage of the building. To this end, air distribution principles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The performance of ventilation and air distribution systems not only influences the indoor air quality directly [11,12], but also strongly affects the total energy consumptions in buildings [13]. Among the evaluation indices referring to ventilation and air distribution systems, there are airflow patterns (such as trajectory, impingement, separation, circulation, reattachment, buoyancy, vortices etc) and airflow field (temperature, velocity and pressure).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of ventilation and air distribution systems not only influences the indoor air quality directly [11,12], but also strongly affects the total energy consumptions in buildings [13]. Among the evaluation indices referring to ventilation and air distribution systems, there are airflow patterns (such as trajectory, impingement, separation, circulation, reattachment, buoyancy, vortices etc) and airflow field (temperature, velocity and pressure).…”
Section: Introductionmentioning
confidence: 99%
“…The heating, ventilating, air-conditioning (HVAC) system is very important for buildings in sub-tropical and tropical climates and is a major contributor to energy consumption, 2,[9][10][11] and there have also been reports that air conditioners could have an impact on health of occupants. [12][13][14][15][16][17] As well as the energy consumption and CO 2 emission issue that are associated with the use of HVAC system, the use of refrigerant for air cooling would also pose greenhouse warming (global warming potential, GWP) and stratospheric ozone depletion potential (ODP) problems on the global environment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies have been conducted to investigate the performance of UFAD for heating mode. Tae et al [5] used Energyplus to evaluate the energy performance of the UFAD and MV systems for heating and cooling in the interior zone of an theatre complex. Their study demonstrated that the heating energy consumption for UFAD was lower than that for MV during the winter heating season (from December to January).…”
Section: Introductionmentioning
confidence: 99%